How can we achieve global equity in provision of renal replacement therapy? - Sarah L White; Steven J Chadban; Stephen Jan; Jeremy R Chapman; Alan Cass (Bulletin of the World Health Organization)
There is a significant emerging burden of chronic and end-stage kidney disease in low- and middle-income countries, driven by population ageing and the global epidemic of type 2 diabetes. Sufferers of end-stage kidney disease require ongoing dialysis or kidney transplantation to survive; however, in many low- and middle-income countries, treatment options are strictly limited or unaffordable. Low numbers of maintenance dialysis patients and transplant recipients reflect profound economic and service provision challenges for health-care systems in low- and middle-income countries in sustaining renal replacement therapy programmes. Underdeveloped organ donor and transplant programmes, health system and financing issues, ethical regulation of transplantation and the cost of pharmaceuticals commonly pose additional barriers to the delivery of efficient and cost-effective renal replacement therapy. Development of locally appropriate transplant programmes, effective use of nongovernmental sources of funding, service planning and cost containment, use of generic drugs and local manufacture of dialysis consumables have the potential to make life-saving renal replacement therapy available to many more in need. Select low- and middle-income countries demonstrate more equitable provision of renal replacement therapy is possible outside high-income countries. For other low- and middleincome countries, education, the development of good public policy and a supportive international environment are critical. Prevention of end-stage kidney disease, ideally as part of an integrated approach to chronic vascular diseases, must also be a key objective.